Revision, community and performance: the role of a literary network in the development of Michael Mohammed Ahmad's The Tribe and Luke Carman's An Elegant Young Man. Issue 2 (3rd May 2016) - Neave, Lucy
ABSTRACT: This paper contributes to recent scholarship on writers' networks by assessing how two contemporary Australian writers, Michael Mohammed Ahmad and Luke Carman, used discussion and performance of drafts to develop their first books. Their revisions enabled them to shape not just their fiction, but to formulate a narrative about western Sydney which they could communicate to a national audience. In the following, I describe an interview I conducted with them about their revision practices and their suggestions for each other's manuscripts. In addition, I discuss the writing processes involved in the completion of The Tribe (2014) and An Elegant Young Man (2013), which emerged from a collaborative environment or 'community of practice', and won literary awards.